Shokubutsu da!: A Fun Learning for Young Learners to Learn Japanese - Azizia Freda Savana; Wistri Meisa (Universitas Muhammadiyah Yogyakarta, 2024)
Teaching Japanese to young learners is a challenge. Young learners need exciting media to learn Japanese vocabulary more easily. Hence, we created Shokubutsu da!, an animated video that is a smart learning media packed with exciting stories narrated in Indonesian, except the names of animal or plant characters are all Japanese. The video allows young learners to memorize Japanese vocabulary much more quickly. This research aims to determine the results of applying video learning Shokubutsu da! to young learners, namely kindergarten age. The method used in this study is qualitative-descriptive, which describes the implementation of animated video in class through observation. This study concluded that most children find remembering the Japanese vocabulary of plants and animals easy by watching the animated video Shokubutsu da!. The video can be more practical because young learners can self-learn, allowing them to play the video repeatedly at any time. Furthermore, the children were enthusiastic, as the video allowed them to have fun learning and memorizing Japanese vocabulary.